Formação doutoral em Serviço Social. Contributos para a construção de ciência a partir da análise socio-histórica no caso de Portugal e dos Estados Unidos da América - Mendes, Sandra (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
This paper addresses the creation of the Social Work scientific project based on the sociohistorical analysis of its emergence at the university, in Portugal and in the USA. Its central themes are the institutionalization of Social Work in graduate training as well as the creation and development of the PhD as advanced training. To this end, we explore the institutional determinants guiding the American case and the implementation of the same for the Portuguese case, based on documental analysis of the reports produced by the Agency for Evaluation and Accreditation of Higher Education (A3ES).